Redox Potentials of Disulfide Bonds in LOXL2 Studied by Nonequilibrium Alchemical Simulation - Lin, Lirui; Zou, Haiying; Li, Wenjin; Xu, Li-Yan; Li, En-Min; Dong, Geng (Frontiers in Chemistry, 2021)
Lysyl oxidase-like 2 (LOXL2) is an metalloenzyme that catalyzes oxidative deamination -amino group of lysine. It is found that LOXL2 is a promotor for the metastasis and invasion of cancel cell. Disulfide bonds are important components in LOXL2, they act as a stabilizing role for protein structure or a functional role for regulating protein bioactivity. The redox potential of disulfide bond is one important property to determine the functional role of disulfide bond. In this study, we have calculated the reduction potential of all the disulfide bonds in LOXL2 by Non-equilibrium alchemical simulations. Our results show that seven of seventeen disulfide bonds have high potential between −185 and −296 mV, and could have functional role, viz., Cys573−Cys625, Cys579−Cys695, Cys657−Cys673 and Cys663−Cys685 in the catalytic domain, while Cys351−Cys414, Cys464−Cys530 and Cys477−Cys543 in the scavenger receptor cysteine-rich domains (SRCRs). The Cys351−Cys414 bond are predicted to act as allosteric function, which is related to the ability of metastasis and invasion of cancer cell. Other functional bonds are of catalytic role related to the enzyme activity. The rest of ten disulfide bonds are predicted to act as structural function. Our study is of importance for the classification of disulfide bonds in LOXL2, and can be utilized for the drug design targeting to the cysteine residue in LOXL2.